Pengetahuan Ibu Hamil melalui edukasi menggunakan aplikasi E-Modul tentang pemenuhan kesejahteraan ibu dalam upaya mencegah stunting di Puskesmas Mangasa Makassar - Afriani Afriani; Fitriati Sabur; Wirawati Amin (Direktorat Politeknik Kesehatan Makassar, 2024)
Stunting can also occur before birth and is caused by very poor nutritional intake during pregnancy, very poor eating patterns, low quality food in line with the frequency of infections so that it can inhibit growth. One of the efforts to prevent children from being born with stunting requires the role of many parties, including the role of Human Resources for Social Welfare Organizers, who act as educators, motivators and mobilizers. Including the role of family and society to improve the welfare of pregnant women by fulfilling their basic needs. The general objective of this research is to find out efforts to prevent stunting in pregnant women through education using the E-module application about fulfilling maternal welfare at the Mangasa Makassar Community Health Center. This research used a pre-experimental design with one group pretest - posttest. The population in this study was 55 pregnant women at the Mangasa Health Center, Makassar. The process of collecting data with a questionnaire using Google Form in the form of Quizzizz. The data was then analyzed to determine the knowledge of pregnant women using the E-module regarding fulfilling maternal welfare using the T Paired test. The research results showed that there was an increase in knowledge of pregnant women through education using the E-module application and quizizz via Google form regarding fulfilling maternal welfare at the Mangasa Makassar Health Center with a value of p=0.000. It is hoped that midwives and families will provide assistance regarding the fulfillment of maternal welfare during pregnancy in an effort to prevent stunting.